2016
DOI: 10.1182/blood.v128.22.4813.4813
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index Tomograms and Dynamic Membrane Fluctuations of Red Blood Cells from Patients with Diabetes Mellitus

Abstract: Background: Diabetic effects on blood rheology are important topics and have been extensively investigated. In particular, it has been known that diabetic RBCs exhibit significantly deteriorated deformability compared to healthy RBCs. Despite the importance of previously measured mechanical properties of diabetic RBCs, several problems remain to be elucidated. First, conventional techniques have difficulties in measuring intrinsic properties of individual cells. Detailed quantification of diabetic alteration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
(46 reference statements)
1
21
0
Order By: Relevance
“…The number of patients diagnosed with T2DM is 64 with a mean age of 61 5 13.7 years, compared to 72 patients with a mean age of 52 5 17.8 years in controls. The blood glucose parameters, hemoglobin A1c (HbA1c), and fasting blood glucose (FBG) are significantly higher in diabetics (HbA1c ¼ 7.66 5 1.41% and FBG ¼ 144.5 5 48.9 mg/dL) compared to the controls (HbA1c (61) shows a reduction in the membrane fluctuation of diabetic red cells, but there was no statistical difference in volume and surface area distributions of nondiabetic and diabetic RBCs. Although the alteration in the size and shape of diabetic RBCs is still debatable and probably dependent on glycemic control of the study subjects, we considered extreme values for S/V that were reported by Jin et al (57).…”
Section: Rbc Modelsmentioning
confidence: 99%
“…The number of patients diagnosed with T2DM is 64 with a mean age of 61 5 13.7 years, compared to 72 patients with a mean age of 52 5 17.8 years in controls. The blood glucose parameters, hemoglobin A1c (HbA1c), and fasting blood glucose (FBG) are significantly higher in diabetics (HbA1c ¼ 7.66 5 1.41% and FBG ¼ 144.5 5 48.9 mg/dL) compared to the controls (HbA1c (61) shows a reduction in the membrane fluctuation of diabetic red cells, but there was no statistical difference in volume and surface area distributions of nondiabetic and diabetic RBCs. Although the alteration in the size and shape of diabetic RBCs is still debatable and probably dependent on glycemic control of the study subjects, we considered extreme values for S/V that were reported by Jin et al (57).…”
Section: Rbc Modelsmentioning
confidence: 99%
“…Furthermore, since the RI value of most biological specimen is linearly proportional to protein concentration [13,14], ODT provides quantitative information including protein concentration and dry mass. For these reasons, there are growing numbers of biological and medical studies employing ODT to investigate the physiology of various samples [4] including neuron cells [15,16], red blood cells [17][18][19][20], parasites in host cells [21,22], immune cells [23], bacteria [15,24], gold nanoparticles in live cells [25], embryos [26], live cells in a microfluidic channel [27][28][29], and blood cells in vivo [30].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, variations in the optical dispersion of blood serum may indicate some diseases since it is directly related to changes in blood components, specifically the concentration of albumin and the appearance of its conjugated forms [9][10][11][12] . Recently, it was shown that variations in the blood serum RI could be used as an additional criterion in the analysis of antitumour therapy 13,14 , and RI monitoring for glycated haemoglobin and albumin enables diagnostics of type 2 diabetes and pre-diabetic status 15,16 .…”
Section: Introductionmentioning
confidence: 99%